Edukasi Penerapan Website Produk Berbasis Wix Builder pada Nadhifa Shop Kota Sorong - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Charliany Hetharia; Jalminj Tindage; Habel S.J. Rieuwpassa (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
The Community Service Program conducted for Nadhifa Shop, a small business facing challenges in promoting its products due to the underutilization of digital media, especially a website. The goal of this program is to assist Nadhifa Shop in expanding its market reach through the creation and management of a website using Wix Builder. The methods employed include direct training (workshop) on how to create and manage a website, personal mentoring to help the partner overcome technical issues, and simulations and case studies to optimize the website's utilization for their business. The results of the program show that Nadhifa Shop successfully built a website equipped with Home, About, Contact, and Shop menus, along with a real-time chat feature for interacting directly with customers. The partner expressed satisfaction with the results, as the website not only simplifies product management but also helps enhance customer interaction and broaden market reach. Therefore, digital management through a website has proven to be an effective solution for Nadhifa Shop's business growth in the digital era.